Hybrid Retrieval Reduces Hallucinations in Phi-3-Mini and Mistral-7B on Religious Domain Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 15 peer-reviewed papers addressing the following research question: How do different RAG retrieval strategies (e.g., dense vs. sparse vs. hybrid) affect hallucination rates in Phi-3-mini and Mistral-7B when evaluated on long-context religious domain benchmarks. 12 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.4/10. This report is a m
Machine-generated literature synthesis.